Dressed Up to the Nines: The Interplay of Phytohormones Signaling and Redox Metabolism During Plant Response to Drought - Douglas Jardim-Messeder; Ygor de Souza-Vieira; Gilberto Sachetto-Martins (Plants)
Plants must effectively respond to various environmental stimuli to achieve optimal growth. This is especially relevant in the context of climate change, where drought emerges as a major factor globally impacting crops and limiting overall yield potential. Throughout evolution, plants have developed adaptative strategies for environmental stimuli, with plant hormones and reactive oxygen species (ROS) playing essential roles in their development. Hormonal signaling and the maintenance of ROS homeostasis are interconnected, playing indispensable roles in growth, development, and stress responses and orchestrating diverse molecular responses during environmental adversities. Nine principal classes of phytohormones have been categorized: auxins, brassinosteroids, cytokinins, and gibberellins primarily oversee developmental growth regulation, while abscisic acid, ethylene, jasmonic acid, salicylic acid, and strigolactones are the main orchestrators of environmental stress responses. Coordination between phytohormones and transcriptional regulation is crucial for effective plant responses, especially in drought stress. Understanding the interplay of ROS and phytohormones is pivotal for elucidating the molecular mechanisms involved in plant stress responses. This review provides an overview of the intricate relationship between ROS, redox metabolism, and the nine different phytohormones signaling in plants, shedding light on potential strategies for enhancing drought tolerance for sustainable crop production.